ANALYSIS OF CHARACTERISTICS OF PAIN IN PHANTOM LOWER LIMP AMPUTATIONS (Fiep Bulletin - online, 2011)
Amputation is defined as withdrawal, usually surgery, all or part of a committed member of the body. Most amputees report the presence of phantom pain after surgery, and pressure sensations, tingling and sometimes numbness, limb amputated as a hallucination due to the difficulty in accepting the mutilation, setting the phantom sensation, like a dream or desire to preserve the anatomical integrity of body. This study aimed to analyze the characteristics of phantom pain presented in unilateral lower-limb amputations. We conducted a direct and an individual questionnaire formulated by the researcher, composed 11pergutas to patients treated at the rehabilitation center of Assisi School Gurgacz in the period from July to August 2010. Of the 25 patients interviewed 17 (68%) had transtibial amputation and 8 (32%), transfemoral amputation, with a mean age of 58.02 men and 57.40 among women, for the main features of phantom sensation, are among The most cited the tingle in the pit and pulse rate.
Keywords: amputation; phantom limb pain; lower limbs